2023
DOI: 10.1021/acs.iecr.3c00488
|View full text |Cite
|
Sign up to set email alerts
|

Novel Correlation for Critical Speed for Solid Suspension in Stirred Tanks Developed Using Machine Learning Models Trained on Literature Data

Abstract: Critical speed for solid suspension (N js ) in stirred tanks is an important design parameter in several chemical processes. There is a need to develop a generalized correlation that applies to a broad range of literature data. Also, the literature lacks a comparative study of different machine learning (ML) models for the prediction of N js . In this paper, 3240 data points have been extracted from 35 papers on solid suspension and N js has been modeled as the dependent variable, initially using ML models. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The detailed modeling framework of all algorithms was explained in Joshi et al (2023) . The following subsections briefly explain the algorithms those were used in this work.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The detailed modeling framework of all algorithms was explained in Joshi et al (2023) . The following subsections briefly explain the algorithms those were used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…A brief overview on machine learning applications to design the multiphase reactors was given in previous study . It has been found that a study on machine learning correlations to correlate Sh () or k SL .25em ( normalm normals ) for agitated vessels is absent in the literature.…”
Section: Literature Surveymentioning
confidence: 99%
See 3 more Smart Citations